1992
DOI: 10.1177/154193129203601814
|View full text |Cite
|
Sign up to set email alerts
|

Target Acquisition in Cluttered Environments

Abstract: The relationship of human target acquisition times and detection probabilities to electronically measured visual clutter was investigated. Ninety computer-generated scenes simulating infrared imagery and containing different levels of clutter and zero, one, two, or three targets were produced. Targets were embedded in these scenes counterbalancing for range and position. Global and local clutter were measured using both statistical variance and probability of edge metrics. Thirty-three aviators, tankers, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…We can see that the SV metric is proposed on the assumption that the visual system is sensitive to the areas with high gray-level variability. Many experiments have showed that SV is suitable for most natural scenes, but could not quantify the urban environment accurately [13], and is poor in predicting overall search time [14]. Silk proposed an improved metric (SSV) [15] of SV by fully considering the difference between every pixel and its neighborhood region through the whole clutter image.…”
Section: Introductionmentioning
confidence: 99%
“…We can see that the SV metric is proposed on the assumption that the visual system is sensitive to the areas with high gray-level variability. Many experiments have showed that SV is suitable for most natural scenes, but could not quantify the urban environment accurately [13], and is poor in predicting overall search time [14]. Silk proposed an improved metric (SSV) [15] of SV by fully considering the difference between every pixel and its neighborhood region through the whole clutter image.…”
Section: Introductionmentioning
confidence: 99%
“…These oscillations have been seen at short times in other experiments, notably a 1993 experiment conducted at the Human Engineering Laboratory, Aberdeen, MD [Birkmire et al (1992)]. They have been simulated numerically in a Monte Carlo simulation by J.F.…”
mentioning
confidence: 99%
“…Such a result indicates that factors such as expectations and other sources of contextual scene information may be as important as image variance in determining performance in some situations. Birkmire, Karsh, Barnette, and Pillalamarri (1992) found that global SV was a poor predictor of overall search time. When SV was calculated for blocks of a display, Rotman, Kowalczyk, and George (1994) found that SV did not correlate highly with eye movements (i.e., fixations to regions of high clutter) in search.…”
Section: Williamsmentioning
confidence: 99%
“…Unfortunately, also like SV, the POE metric fails to accurately predict response time (Birkmire et al, 1992) and fixation location during search (Rotman et al, 1994a). Presumably, a problem with the metric is that although edges of objects lead to edge-defined pixels, edge-defined pixels do not necessarily indicate the edges of real objects.…”
Section: Williamsmentioning
confidence: 99%